Watson Kota Bharu / Muhammad Haikal Mohd Asmawi - Mohd Asmawi, Muhammad Haikal (2021)
In this case study I’ll be doing on Watson Personal Care stores (Malaysia) Sdn. Bhd located at Jalan Sultan Yahya Petra, Kota Indah, 15200 Kota Bharu, Kelantan. Watson is an integrated global specialty pharmaceuticals company and is one of best known trading names in Malaysia. Originally the company began as a small dispensary in Guangzhou, China in 1828, opened in Hong Kong in 1841, and it proceeded to become one of the first companies in the world that produces the carbonated soft drinks. In 1994, Watsons expanded to Malaysia. Watson has continue to expanded into many branches in Malaysia. There are about 90 stores outlets in Malaysia and Singapore which will be expected to be increases steadily per year. Watson’s regularly carry more than 25,000 items that is sourced from over 20 centuries, also including its own label that is GIANETTO. Some of the items that contributedthe most profits to the Watson’s are Personal Care, Lifestyle, Beauty Products and Health and Fitness. The store ranges in size from the 2,000 to 12,000 square feet with the ideal size being a 5,000 square ft.